Abilities of children with language developmental disorders in perceiving phonological, grammatical, and semantic structures - Georgiou, Georgios P.; Theodorou, Elena (My University, 2022)
This study aims to investigate the perception of phonological, grammatical, and semantic structures by 8 children (age range: 8;2–9;5) with developmental language disorders (DLD). Another 8 age-matched (age range: 8;4–10;0) typically developing (TD) children served as controls. The results demonstrated that children with DLD had lower performance than children with TD in the phonology and grammar tests, corroborating earlier findings, which reported difficulties of children with DLD in discriminating voicing contrasts and perceiving grammatical structures. However, both groups had similar performance in the semantic test. The absence of semantic atypicality can be explained possibly due to the simplicity of the sentences included in the test. The study offers important clinical implications for the identification and treatment of the disorder.
Keywords: Language Disorder; Perception